Pembelajaran Praktik Dalam Peningkatan Pemahaman Peserta Didik Mapel Fiqih di MTs Roudlotut Tholibin Kediri - Qurrotul Ainiyah; Ahmad Ari Tohari (LP3M STIT Al Urwatul Wutsqo Jombang, 2021)
The purpose of this research is to describe how the practical learning process is in increasing students understanding?, How to increase students' understanding through practical learning in class VIII Madrasah Tsanawiyah Roudlotut Tholibin Kediri?, What are the supporting and inhibiting factors in improving students' understanding through practical learning at Madrasah Tsanawiyah Roudlotut Tholibin Kediri ? This study uses a type of field research (fieldreasearch)and using a qualitative descriptive approach, with the design of data collection through interviews, observation and documentation. Furthermore, data analysis was carried out using descriptive qualitative analysis methods. It was found that: in class VIII MTs Roudlotut Tholibin Kediri used the practical method in order to improve student understanding, in each practice carried out through 3 stages, namely, the preparation stage, the implementation stage and the final stage in accordance with the learning implementation plan (RPP). then it was found that the impact of students who took part in practical learning activities had a high cognitive level compared to students who only studied material, there was also good interaction between teachers and teachers, teachers and students and students and students themselves. The supporting factors in practical learning are teachers, parents, environment, strength or cooperation between teachers, regulatory points. Meanwhile, the inhibiting factors are friends and students themselves. So, from the explanation above, it is proven that practical learning can improve students' understanding of maple fiqh class VIII MTs Roudlotut Tholibin.